(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
This paper presents an overview of the fundamentals used to more accurately assess organizational performance, identifying bottlenecks and performance conflicts, a detailed organizational analysis based on a formal organization model should be performed. Furthermore, a formal organizational model is the basis for many automated processes within companies, for example computer-integrated manufacturing; In addition to providing a basis for cooperation between its internal areas, and even other companies.